Does time to esophagectomy following neoadjuvant immunochemotherapy for locally advanced esophageal squamous cell carcinoma affect outcomes? - Hong, Zhi-Nuan; Huang, Zhixin; Weng, Kai; Lin, Jihong; Kang, Mingqiang (Frontiers in Immunology, 2022)
Objectives Neoadjuvant immunochemotherapy (nICT) is a novel pattern for locally advanced esophageal squamous cell carcinoma (ESCC), and the time to surgery (TTS) is recommended as 4-6 weeks. However, there were some patients with prolonged TTS(>6weeks) .This study aimed to explore whether prolonged TTS (>6weeks) would affect the outcomes. Methods Patients diagnosed with locally advanced ESCC between January 2020 and March 2022 and undergoing esophagectomy following nICT were identified based on a prospectively collected database. Primary outcome measures were pathological complete response (pCR) and disease free survival (DFS), and the secondary outcomes were 30-day postoperative mortality and morbidity, surgical time, postoperative hospital stay, and hospital expense. Results Total 95 patients were included for analysis, with 52 patients in standard TTS group and 43 patients in prolonged TTS group. The clinical and demographic characteristics of the two groups were comparable. The prolonged group had a median 18 days longer TTS(P<0.001). The pCR rate was 23.08% (12/52) in standard group and 16.28% (7/43) in prolonged group (P=0.41). Univariate regression analysis further indicated that TTS wasn’t an independent factor to predict pCR (P=0.33). The median follow-up time was 10.5 months in the standard TTS group and 11.2 months in the prolonged TTS group. Total five recurrence occurred with two events in the standard TTS group and three events in the prolonged TTS group, and no significant difference was observed in DFS(P=0.60). Both groups were comparable in postoperative hospital stays, total hospital stay, hospital expenses, and comprehensive complications index (CCI). The complications and major complications were also similar in both groups. Spearman test further indicated that there was no linear correlation among TTS with hospital expenses, postoperative hospital stays, hospital stay, CCI index, lymph nodes moved number, or surgical time, with a p value 0.48, 0.63, 0.80, 0.92, 0.09, 0.38 respectively. Conclusions Based on present evidence, TTS after completion of nICT is not of major importance with regard to pathological response, disease-free survival and short-term postoperative outcomes.